The influence of the european structural founds on the sport and recreational infrastructure development. The case of Lębork Poviat - Parzych, Krzysztof (Journal of Education, Health and Sport, 2017)
The aim of this study was an analysis of the influence of the european founds on the tourist infrastructure development. As case study the area of the Lebork poviat was used. It was made an analysis of the most important realisations of the tourist infrastructure development in the town Lebork and other localities of the Lebork poviat. Besides it the analysis of the influence of the tourist and recreation development on the social live. Results show very important role of the infrastructure tourist development built from the european founds on the socjety of Lebork poviat.